Substance Use Disorder, Bail Reform, and Failure to Appear in Court: Results From a Naturalistic Study - Kopak, Albert M. (Journal of drug issues, 2023)
Most adults processed through local correctional facilities report symptoms consistent with substance use disorder and there is growing interest in bail reform to reduce or eliminate financial conditions as a requirement for release from detention in local jails. These practices are endorsed for their ability to reduce jail populations and enhance judicial efficiency, but failure to appear in court has become a major area of concern under these new procedures. The current study examined the associations between substance use disorder, financial release conditions, and failure to appear in court in the context of a naturalistic study of bail reform in one judicial district. Multivariate logistic regression results demonstrate significantly higher odds of failure to appear in court among adults with substance use disorder who received a nonfinancial release from jail. Findings suggest bail reform initiatives must address substance use disorder and provide person-centered services during the pretrial release period to become effective.